45 Rivaroxaban vs. dabigatran or warfarin in real-world observational studies of stroke prevention in atrial fibrillation: systematic review and meta-analysis. (5th June 2017) - Bai, Ying; Deng, Hai; Shantsila, Alena; Lip, Gregory YH
Abstract : Objective: To evaluate the effectiveness and safety of rivaroxaban in real-world practice compared with dabigatran (R vs. D) or with warfarin (R vs. W) for stroke prevention in atrial fibrillation (AF). Methods and Results: 17 studies were included after a thorough search in PubMed for studies reporting comparative effectiveness and safety of R vs. D(3), R vs. W (11) or both conditions (3)for stroke prevention in AF. Overall, the risks of ischaemic stroke (IS)/systematic thromboembolism (TE) with rivaroxaban were similar compared with dabigatran (Figure 1) IS/TE: (HR:1.02, 95% CI: 0.91–1.13, I2=70.2%, n=5), but were significantly reduced when compared to warfarin. IS/TE:(0.75, 0.64–0.85, I2=45.1%, n=9). Major bleeding risk was significantly higher with rivaroxaban than dabigatran (Figure 2) (1.38, 1.27–1.49, I2=26.1%, n=5), but similar to warfarin (0.99, 0.91–1.07, I2=0.0%, n=6). Rivaroxaban was associated with increased all-cause mortality and gastrointestinal bleeding (GIB), but similar risk of acute myocardial infarction (AMI) and intracranial bleeding (ICB) compared with dabigatran. When compared with warfarin, rivaroxaban was associated with similar risk of any bleeding, mortality and AMI, but a higher risk of GIB and lower risk of ICB. Conclusions: In this systematic review and meta-analysis, rivaroxaban was as effective as dabigatran, but was more effective than warfarin for the prevention of IS/TE in AF patients. Major bleeding risk was significantly higher with rivaroxaban than dabigatran, as was all-cause mortality and GIB. Rivaroxaban was comparable to warfarin for major bleeding, with an increased risk in GIB and decreased risk of ICB.